2015
DOI: 10.11648/j.jfns.20150303.13
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Intervention- The Impact on Vitamins and Minerals Intake to Overweight and Obese Patients

Abstract: Background and Aims-To evaluate the impact of nutritional intervention on vitamins and minerals from intake food and anthropometric parameters at overweight and obese patients. Material and methods-To a sample of 40 overweight and obese patients we evaluated the nutritional content of food intake (kilocalories, macro and micronutrients) before and after a low caloric diet. We also measured anthropometric parameters like weight, body mass index, body fat, percent of body fat, abdominal circumference and arteria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Other studies showed that the periodontal disease could be accelerated by destructive oxidative factors and final factors of advanced glicolisis [16]. The process is paralled by periodontitis itself as a source of oxidative stress able to modify the level of circulant adipocytokines such as leptin, which is known to accelerate the onset of resistance to insulin and metabolic syndrome [17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…Other studies showed that the periodontal disease could be accelerated by destructive oxidative factors and final factors of advanced glicolisis [16]. The process is paralled by periodontitis itself as a source of oxidative stress able to modify the level of circulant adipocytokines such as leptin, which is known to accelerate the onset of resistance to insulin and metabolic syndrome [17][18][19][20].…”
Section: Resultsmentioning
confidence: 99%
“…Also, it induces insulin resistance and hepatic steatosis over time, diseases directly associated with obesity. [7,10] To remove the excess ECM and allow adipocyte hypertrophy, MMPs play a central part in the control of adipogenesis through the proteolytic activities that takes place during fat mass enlargement.…”
Section: Resultsmentioning
confidence: 99%